Multi-objective optimisation of hydroelectric PMSG considering water-level variation - Jian Gao; Litao Dai; Wenjuan Zhang; Shoudao Huang (The Journal of Engineering, 2019)
The variable hydrological conditions that are found in run-of-the river projects require operations over a wide range of water-level variations. This article develops a novel optimisation strategy for permanent magnet synchronous generator (PMSG) used in hydroelectric plant. The basis of this strategy is a simplified subdomain (SD) analytical model of the surface-mounted PM generator combined with an improved genetic algorithm, which searches the optimal generator parameters that maximise the operating efficiency of generators at different water-level conditions and minimise the material cost. The electromagnetic performances of the optimised generator are investigated and compared with conventional optimal design. It is found that the proposed method allows the emergence of higher performances in variable hydrological conditions.